Motorcycle Safety – the Next Magic Bullet? - Brian Wood (Journal of Road Safety, 2005)
Although motorcycle crashes account for more than 10% of road trauma, motorcycle safety is an area of road safety that has generally been overlooked When I started taking an interest in this subject several years ago I was told that it was adequately taken up under the general road safety message. This does not appear to be the case when comparing our record in motorcycle safety and our general road safety record against other OECD countries. In motorcycle safety we are ranked 6th last whereas at that time we were ranked 6th best for general road safety (ATSB). Had motorcycle safety been adequately taken up in the general road safety message, our record in motorcycle safety would be similar to that of our general record. Whereas our general road safety ranking is not dissimilar to the world’s best, in motorcycle safety the world’s best countries have a fatality rate one third of ours. Therefore, there is significant potential for improvement.